Polyhexamethylene biguanide promotes adaptive cross-resistance to gentamicin in Escherichia coli biofilms - Charron, Raphaël; Lemée, Pierre; Huguet, Antoine; Minlong, Ornella; Boulanger, Marine; Houée, Paméla; Soumet, Christophe; Briandet, Romain; Bridier, Arnaud (Frontiers in Cellular and Infection Microbiology, 2023)
Antimicrobial resistance is a critical public health issue that requires a thorough understanding of the factors that influence the selection and spread of antibiotic-resistant bacteria. Biocides, which are widely used in a variety of settings, may contribute to this resistance by inducing similar defense mechanisms in bacteria against both biocides and antibiotics. However, the strategies used by bacteria to adapt to biocides and develop cross-resistance remain poorly understood, particularly within biofilms -a widespread bacterial habitat that significantly influences bacterial tolerance and adaptive strategies. In this study, we investigated how Escherichia coli biofilms adapted after 28 days of exposure to three biocides: benzalkonium chloride (BAC), N-(3-aminopropyl)-N-dodecylpropane-1,3diamine (TMN) and polyhexamethylene biguanide (PHMB). Interestingly, PHMB exposure led to an increase of gentamicin resistance (GenR) phenotypes in biofilms formed by most of the seven E. coli strains tested. Nevertheless, most variants that emerged under biocidal conditions did not retain the GenR phenotype after removal of antimicrobial stress, suggesting transient adaptation (adaptive resistance) rather than stable mutational resistance. The whole-genome sequencing of variants with stable GenR phenotypes revealed recurrent mutations in genes associated with cellular respiration, including cytochrome oxidase (cydA, cyoC) and ATP synthase (atpG). RT-qPCR analysis revealed an induction of gene expression associated with biofilm matrix production (especially curli synthesis), stress responses, active and passive transport and cell respiration during PHMB exposure, providing insight into potential physiological responses associated with adaptive cross-resistance. In addition, confocal laser scanning microscopy (CLSM) observations demonstrated a global effect of PHMB on biofilm architectures and compositions formed by most E. coli strains, with the appearance of dense cellular clusters after a 24h-exposure. In conclusion, our results showed that the PHMB exposure stimulated the emergence of an adaptive cross-resistance to gentamicin in biofilms, likely induced through the activation of physiological responses and biofilm structural modulations altering gradients and microenvironmental conditions in the biological edifice.